The Stunting Scorecard for Early Prevention: Development and External Validation of a Novel Tool for Predicting Stunting Risk in Children Under 5 Years of Age - Enung Mardiyana; Rini Ambarwati; Fathimath Shifaza (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2022)
Children under five years of age are very sensitive to environmental influences such as inadequate nutrition, lack of stimulation, and other factors. Several types of health problems can hinder the growth process of children under five, one of which is stunting. This study aims to develop a scorecard model for early detection of stunting risk based on stunting factor analysis in the Surabaya City Health Centre work area. The design of this study is conducted in several phases, including the first phase of analyzing risk factors using a case-control design, and the second phase of compiling a scorecard for early detection of stunting risk with a panel of experts. The sample in this study consisted of several mothers and infants, both with and without stunting risk. The sample size is 175 mothers and children under five years of age. The sampling method used was systematic random sampling. The risk factor data were analyzed using the multinomial logistic regression test, and the scorecard was created based on the OR value. The result of this study is the scorecard able to make early detection of stunting risk with a cut-off value is 3.50. It is mean that using the scorecard has a sensitivity of 80% and specificity of 75% to detect the stunting risk of children. The scorecard can be used to determine whether a child is at low or high risk for stunting. This study implies that the scorecard can be used for early detection of stunting risk by mothers, health cadres, and health workers. It is hoped that by using the scorecard, early identification of the risk of stunting can be addressed immediately and interventions can be implemented according to the recommendations and problems that children are experiencing.